Statin safety: myths and reality - Zh. D. Kobalava; S. V. Villevalde; E. K. Shavarova (Кардиоваскулярная терапия и профилактика, 2007)
More frequent statin prescription, to achieve lower target low-density lipoprotein levels, as well as statin dose increase, is associated with inevitable raise in adverse event rates. The article compares statin benefits and the risk of adverse liver, muscle, brain, and kidney effects.